Periodontal Inflammation as a Modifiable Risk Factor for COPD Exacerbations in the Indian Population: A Prospective Cohort Study - Anuj Singh Parihar; Dhairaysheel N. Edake; Sandhya Nema; Manoharmayum Laxmipriya; Shailja S. Vediya; Deepak Kochar; Rashmi Laddha (Journal of Pharmacy and Bioallied Sciences)
Background: Chronic obstructive pulmonary disease (COPD) is a major health concern in India, with exacerbations leading to increased morbidity, mortality, and healthcare costs. Periodontal disease, a chronic inflammatory condition, may affect COPD outcomes by promoting systemic inflammation. This prospective cohort study aimed to investigate the association between periodontal inflammation and the risk of COPD exacerbations in the Indian population. Methods: A total of 2500 participants with established COPD from various regions of India were enrolled and followed for five years. Baseline assessments included comprehensive periodontal evaluations, with measurements of clinical parameters and inflammatory markers (C-reactive protein, interleukin-6). COPD exacerbations were defined as events requiring medical intervention, such as hospitalization, emergency room visits, or changes in medication. Results: Periodontal inflammation, measured by clinical attachment loss and elevated inflammatory markers, was significantly associated with a higher risk of COPD exacerbations (Hazard Ratio [HR] 2.3, 95% Confidence Interval [CI] 1.7–3.1), even after adjusting for confounders. Specific periodontal parameters and inflammatory markers were identified as strong predictors of future exacerbations. Conclusions: This study provides evidence that periodontal inflammation is an independent and potentially modifiable risk factor for COPD exacerbations in the Indian population. Addressing periodontal health as a part of COPD management may offer a novel approach to reduce the frequency and severity of exacerbations, thereby improving quality of life and clinical outcomes.